MENINGKATKAN PEMAHAMAN KONSEP MATEMATIS PESERTA DIDIK MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) - Tiara Moriszka (Departemen Matematika, 2020)
The first goal of learning mathematics is understanding mathematical concepts. Based on observations made in class VII SMP Negeri 31 Padang in the 2019/2020 Academic Year, it was found that students' understanding of mathematical concepts was still low. This can be seen from the acquisition of the completeness of the Daily Assessment of Mathematics for Grade VII students of SMP Negeri 31 Padang for the 2019/2020 academic year. Therefore we need a learning model that can overcome these problems. One learning model that can improve students' understanding of mathematical concepts is the Think Pair Share type cooperative learning model. The purpose of this study was to theoretically describe whether the Think Pair Share (TPS) type of cooperative learning can improve students' understanding of mathematical concepts. This type of research is a literature study on improving understanding of mathematical concepts through the TPS-type cooperative learning model. The conclusion of this study is that the application of TPS-type cooperative learning described in the related article regarding indicators on this ability has a tendency to increase students' understanding of mathematical concepts. Keywords __ TPS, Cooperative Learning, Understanding Of Mathematical Concepts